Obsessive Compulsive Disorder Tokoh Sata Senda dalam Manga Keppeki Shounen Kanzen Soubi!! Karya Touya Tobina. - Prabawati, Dewi Wirasetia (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 3 No 1 (2021)DO - 10.24843/JS.2021.v03.i01.p04, 2021)
This research discusses about “Obsessive Compulsive Disorder Tokoh Sata Senda in Manga Keppeki Shounen Kanzen Soubi!! By Touya Tobina”. The research aims to provide psychology knowledge about Obsessive Compulsive Disorder (OCD). The research metdod used was descriptive analysis. There were five theories used in this research, they were the psychology literature theory by Wellek and Austin (1989), theory of OCD by Wilson (2001) ,Oltmanns and Emery (2003), theory of Cognitive therapy by Aron T Beck (1976) semiotics by Danesi (2007). The result obtained from this research , Sata Senda is suffer from OCD with behavior ( 1) , Washing and Cleaning , (2) Ordering , (3) Checking , (4) Ritual . Physiology, Sata Senda has a neat and reclusive appearance to avoid germ and disease. Psychology, Senda OCD can be seen from his excessive behavior like washing and cleaning, ordering all things around, over checking a things again and again, and do ritual repeatly everyday. Sociologically, Senda OCD can affect people around him like ordering his friends to washing everytime they touch something . The Obsessive Compulsive Disorder in Sata Senda caused by two factors there is internal factors that can from trauma ans stress and external factors that came from people around him. The efforts of Sata Senda figure to decrease his OCD behaviour is from internally is Senda has intention to be a normal person, which is make Senda trying to overcome his OCD by decreasing his anxiety from the things that are surrounding him. Except from Senda desired to control his OCD , his friends has important rule to overcame Senda OCD